2020
DOI: 10.1007/s11096-020-00970-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ acceptance of pharmacists’ interventions in daily hospital practice

Abstract: Background The physicians' acceptance rate of pharmacists' interventions to improve pharmacotherapy can vary depending on the setting. The acceptance rate of interventions proposed by pharmacists located in the hospital pharmacy over the telephone and factors associated with acceptance are largely unknown. Objective To determine the physicians' acceptance rate of pharmacists' interventions proposed over the telephone in daily hospital practice and to identify factors associated with acceptance. Setting A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
4
29
3
Order By: Relevance
“…Previous works have suggested that the clinical impact on patient health of a PI facilitates its acceptance, but these studies had a small sample and did not use the CLEO scale ( Zaal et al, 2020 ). The fact that PIs are significantly more often accepted when they have a major clinical impact on patient health should support the medical attention they generate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have suggested that the clinical impact on patient health of a PI facilitates its acceptance, but these studies had a small sample and did not use the CLEO scale ( Zaal et al, 2020 ). The fact that PIs are significantly more often accepted when they have a major clinical impact on patient health should support the medical attention they generate.…”
Section: Discussionmentioning
confidence: 99%
“…17 Studies on the acceptance rates of pharmaceutical interventions demonstrate great variability of these numbers, with rates between 50% and 99.5% of the total interventions. [18][19][20] This study found an acceptance rate of 83.5% by the medical team in the total of interventions for medication discrepancies, and all the interventions related to unintentional discrepancies were accepted. The interventions that were not accepted were related to discrepancies in which there was no record in the medical chart of the clinical reason for their occurrence, which warns of the need for institutional initiatives to optimize the medical record of medication reconciliation, including continuing education actions.…”
Section: Resultsmentioning
confidence: 99%
“…The overall acceptance rate in our observational study (74.3%) was comparable with previously reported values between 52% and 100% in studies assessing interventions proposed by pharmacists. Previous studies have already shown that verbally communicated recommendations are more likely to be accepted by physicians (Zaal et al., 2020). In the future, it might therefore be commendable to contact the physician by phone in case of non‐acceptance.…”
Section: Discussionmentioning
confidence: 97%